Screening for Biosurfactant Production from Lactic Acid Bacteria isolated from African fermented milk ‘Wara’ - Balogun, S. A.; Ogunbanwo, S.T.; Oni, F. F. (UMYU Journal of Microbiology Research)
Lactic Acid Bacteria (LAB) from ‘wara’ an African fermented milk (cheese)was screened for the production of surface-active agent (biosurfactant) from five species of Lactobacillus. Lactobacillus plantarum, Lactobacillus fermentum, Lactobacillus brevis, Lactobacillus casei, and Lactococcus lactis using red blood cell haemolysis test, emulsification index and oil spreading assay. Lactobacillus fermentum and Lactobacilli brevis showed the largest zone of heamolysis when screened on blood agar. The highest emulsification index of 20% was by Lactobacillus plantarum while the least emulsification index of 11% was recorded for Lactobacillus casei. All the isolates showed surface activity after being grown in 2%, 4% and 8% glucose and lactose respectively.